Academic Benefits from Parental Involvement are Stratified by Parental Socioeconomic Status: A Meta-analysis. - Tan, Cheng Yong; Lyu, Meiyan; Peng, Baiwen (Parenting: Science & Practice)
Objective. The present study critically evaluates the assumption that parental involvement benefits students' achievement regardless of their socioeconomic status (SES). Design. A meta-analysis of 98 studies published 2000–2017 examines if patterns of associations between 11 specific parental involvement variables and the academic achievement of K-12 students vary with parental SES as measured by educational level. Results. Results showed that (1) six specific aspects of parental involvement, namely parental academic expectations, parental support for child learning, parent-child discussion of school matters, parental participation in school governance and events, parent and child reading together, and parental emphasis on education, were positively associated with student achievement; (2) subtle forms of parental involvement were most strongly associated with student achievement, followed by home- and school-based involvement; (3) parental learning support at home, parental academic emphasis, and parent-teacher communication had stronger association with the achievement of students whose parents were more educated; (4) parent-teacher communication and parental academic emphasis for college-educated parents did not additionally benefit student achievement when compared to these involvement activities for parents with at most Grade-12 education; and (5) parental involvement was more strongly associated with the linguistic achievement of students with highly educated parents. Conclusions. These results provide evidence that some benefits of parental involvement are stratified by familial SES.